V-N microalloyed ultrahigh-strength weathering steel with specification smaller than or equal to 10 mm and production method of V-N microalloyed ultrahigh-strength weathering steel
By adopting V-N micro-alloy technology in weather-resistant steel to form nano-analysis and optimization of ferrite, it solves the problem of unable to take care of the existing weather-resistant steel between high intensity and lightweight. Steel is suitable for a variety of applications.
Patent Information
- Application Number
- CN202411475403.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
Existing weather-resistant steels are difficult to take into account both high strength and lightweight, and are prone to casting cracks during the production process.
The V-N micro-alloy super high-weather resistance is used with ≤10mm specifications. Through low C, NB+V-N composite micro-alloy design, it forms a nano TIC, (Ti, NB) C to make a phase, fix the free C, reduce the FE3C content And to accurately control the content of elements such as MN, CR, Ni, V to optimize the body and improve the mechanical properties of steel.
It achieves the high strength of steel (yield strength is not less than 850MPa) and good toughness, reduces the risk of slab cracks during the production process, and is suitable for railway vehicles, containers, roads and bridges and other fields.
Smart Images

Figure CN119351897A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a VN microalloyed ultra-high strength weathering steel with a specification of ≤10 mm and a production method thereof. Background Art
[0002] Weathering steel, also known as atmospheric corrosion resistant steel, is a low alloy steel between ordinary steel and stainless steel. It is widely used in railways, vehicles, bridges, towers, photovoltaics, high-speed engineering and other steel structures that are exposed to the atmosphere for a long time. Under the background of "increasing speed, reducing deadweight, and increasing load" in my country's railway freight transportation, high strengthening and lightweight are the development direction of weathering steel for railway containers. At present, the steel plates mainly used for weathering steel for railway containers are weathering steels with yield strengths of 345MPa and 450MPa. The unit weight is heavy, and the amount of steel used and transportation costs are high. Without reducing the performance of the material, increasing the strength of the steel and reducing the thickness of the steel is an effective way to achieve lightweight components in the corresponding field.
[0003] The Chinese invention patent with publication number CN102766826B discloses a method for preparing vanadium-nitrogen microalloyed high-strength weathering steel. The mass percentage of the steel is: 0.08%≤C≤0.13%, 0.15%≤Si≤0.50%, 1.55%≤Mn≤2.00%, P≤0.020%, S≤0.008%, 0.25%≤Cu≤0.50%, 0.50%≤Cr≤0.70%, 0.20%≤Ni≤0.30%, 0.12%≤V≤0.20%, 0.031%≤N≤0.045%, 0.01%≤Re≤0.03%, and the rest is Fe. The invention relates to a steel plate with a thickness of ≤8mm, a yield strength of ≥650MPa, a tensile strength of ≥900MPa, an elongation of ≥15%, a yield strength ratio of ≤0.75, and qualified bending performance (D=2a), but does not involve toughness indicators, and the N content in the chemical composition reaches 0.031% to 0.045%. In actual production, the N content in this range is very likely to cause cracks in the ingot during continuous casting, so it is not suitable for continuous casting production.
[0004] The Chinese invention patent with publication number CN101161849A discloses a method for improving the performance of 700MPa grade VN microalloyed high-strength weathering steel. The mass percentage content is: C≤0.08%, 0.25%≤Si≤0.75%, 0.20%≤Mn≤2.0%, P≤0.025%, S≤0.040%, 0.25%≤Cu≤0.60%, 0.30%≤Cr≤1.25%, Ni≤0.65%, 0.02%≤V≤0.20%, 0.015%≤N≤0.030%. The invention adopts a thin slab continuous casting and rolling short process, and utilizes VN microalloying technology. In the thin slab continuous casting and rolling process, VN and V (C, N) nano-precipitates in the casting process refine the grains and produce 700MPa high-strength weathering steel plates based on the precipitation strengthening principle. However, the invention involves a thickness of ≤8.0mm and does not involve a thickness specification of 10mm. Affected by the specification effect, plates of different thicknesses have different requirements on material composition and rolling process, and when the N content is about 0.03%, the toughness of the steel plate will decrease.
[0005] The Chinese invention patent with publication number CN101161843A discloses a method for improving the utilization rate of vanadium alloy in VN microalloyed high-strength steel. This method targets the chemical composition range of molten steel in VN microalloyed high-strength steel, reduces the V / N ratio to 4≤V / N≤6, increases the precipitation amount of carbonitrides in VN microalloyed high-strength steel by controlling the V / N ratio, reduces the amount of microalloying element V, increases the alloy utilization rate of V, increases the production cost of steel, and improves product competitiveness. Although this invention improves the alloy utilization rate of V, in terms of process implementation, it mainly focuses on precipitation strengthening, solid solution strengthening, and fine grain strengthening, and does not improve phase transformation strengthening and dislocation strengthening through reasonable process design. Summary of the invention
[0006] In order to overcome the above-mentioned deficiencies of the existing weathering steel, the technical problem to be solved by the present invention is to provide a VN micro-alloyed ultra-high strength weathering steel with a specification of ≤10mm and a production method thereof.
[0007] The technical solution adopted by the present invention to solve its technical problem is:
[0008] A VN microalloyed ultra-high strength weathering steel with a specification of ≤10mm, the strength of the weathering steel being not less than 850Mpa, comprising the following components in percentage by mass: 0.030≤C≤0.050%, 0.10%≤Si≤0.20%, 1.20%≤Mn≤1.30%, 0.050%≤P≤0.060%, S≤0.003%, 0.010%≤Als≤0.050%, 0.90%≤Cr≤1.00%, 0.15%≤Ni≤0.20%, 0.30%≤Cu≤0.35%, 0.060%≤V≤0.070%, 0.020%≤Nb≤0.030%, 0.0060%≤N≤0.0070%, O≤0.0020%, and the balance being Fe and unavoidable impurities.
[0009] A method for preparing VN microalloyed ultra-high strength weathering steel with a specification of ≤10 mm, using the above-mentioned strong weathering steel, requiring the strength to be not less than 850 MPa, and further comprising the following steps:
[0010] Step 1: sequentially carry out hot metal desulfurization, converter, RH vacuum treatment and LF refining to obtain molten steel that meets the chemical composition design requirements;
[0011] Step 2, feeding the molten steel obtained in step 1 into a continuous casting machine for slab continuous casting;
[0012] Step 3: heating the slab after continuous casting at a temperature of 1250±10°C for a heating time of 220 to 300 minutes, wherein the holding time is ≥35 minutes;
[0013] Step 4: Rough rolling the heated slab, the thickness of the intermediate slab at the rough rolling outlet is 40-55 mm, and then the intermediate slab is coiled and scaled using a hot coil box;
[0014] Step 5: Finish rolling the intermediate billet. When the finished product thickness is less than 6.0 mm, the finishing rolling inlet temperature is 1030-1080°C, and the final rolling temperature is 840-870°C; when the finished product thickness is 6.0-10.0 mm, the finishing rolling inlet temperature is 980-1020°C, and the final rolling temperature is 850-880°C;
[0015] Step 6: Cool the slab after finish rolling and then curl it at a temperature of 470-500°C. After coiling, place it in a slow cooling pit and slowly cool it to room temperature.
[0016] Furthermore, in the converter process of step one, high carbon ferromanganese is used for manganese addition and high manganese ferrochromium is used for chromium addition without decarburization. Decarburization is performed during RH vacuum treatment, and then quantitative and precise carbon addition is performed in LF.
[0017] Furthermore, before coiling in step six, the steel strip after finish rolling is laminar cooled by a front-stage rapid cooling method, the laminar cooling rate is ≥60°C / s, and the midpoint temperature is 520-550°C.
[0018] The beneficial effects of the present invention are as follows: the present invention adopts a composition design of micro-low C, Nb+VN composite microalloying, and forms nano-TiC and (Ti, Nb)C precipitation phases by adding Ti and Nb, which can fix free C and reduce the Fe3C content, while achieving the purpose of strengthening ferrite, and optimizing ferrite by precisely controlling the content of elements such as Mn, Cr, Ni, and V, thereby improving the mechanical properties of steel. During preparation, through precise heating, rolling, front-end rapid cooling, medium-high temperature coiling and other processes, the obtained metallographic structure is a steel strip with bainite (B) + acicular ferrite structure (AF) + nano-precipitation phase (V(C, N), NbC), and the mechanical properties are R eL ≥720MPa, R m ≥850MPa, A≥17%, can be widely used in railway vehicles, containers, roads and bridges and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is the metallographic organization diagram of the present invention. DETAILED DESCRIPTION
[0020] The present invention is further described below in conjunction with embodiments.
[0021] The invention provides a VN microalloyed ultra-high strength weathering steel with a specification of ≤10 mm, the strength of which is not less than 850 MPa, and the steel comprises the following components in percentage by mass: 0.030≤C≤0.050%, 0.10%≤Si≤0.20%, 1.20%≤Mn≤1.30%, 0.050%≤P≤0.060%, S≤0.003%, 0.010%≤Als≤0.050%, 0.90%≤Cr≤1.00%, 0.15%≤Ni≤0.20%, 0.30%≤Cu≤0.35%, 0.060%≤V≤0.070%, 0.020%≤Nb≤0.030%, 0.0060%≤N≤0.0070%, O≤0.0020%, and the balance is Fe and unavoidable impurities.
[0022] The role of each element component is:
[0023] C: must have a certain content in order to promote the formation of carbide strengthening phase, thereby ensuring the strength level of the steel strip. When its content is too high, the precipitated carbide particles will increase, which is not conducive to the hole expansion performance of the steel plate; when its content is too low, the strength cannot meet the design requirements. The present invention controls the C content between 0.030% and 0.050%, and forms nano-TiC and (Ti, Nb) C precipitation phases by adding Ti and Nb, fixes free C, reduces the Fe3C content, and achieves the purpose of strengthening ferrite.
[0024] Si: It has a solid solution strengthening effect, which can simultaneously improve the strength and elongation of the steel strip and improve the formability of the steel strip. Usually, the silicon content should not be less than 0.30%. However, when the Si content is high, Fe2SiO4 red rust is easily generated on the surface of the steel strip, which is difficult to remove during pickling. In order to improve the surface quality of the steel strip and reduce the difficulty of smelting by the steel plant itself and the difficulty of removing red rust iron scale by users, the present invention designs the Si content to be 0.10% to 0.20%.
[0025] Mn: It is a solid solution strengthening element. According to the strength requirements of this steel grade, when the content is too low, the strength will not meet the design requirements; when the content is too high, the proportion of pearlite will increase, and high Mn content will easily lead to Mn component segregation in the ingot, which is one of the main reasons for the appearance of banded structure in the steel strip, and the banded structure will cause the plastic toughness of the steel strip to drop sharply. At the same time, for carbon manganese steel, the interaction between C and Mn has a certain influence on the formation and distribution of pearlite structure. When the content of both is too high, coarse pearlite and banded structure are easily generated. Therefore, under the premise that the strength meets the design requirements, the C content and Mn content are designed to be as low as possible. In the present invention, the Mn content is 1.20% to 1.30%.
[0026] P: As the strongest element for strengthening ferrite, it has strong solid solution strengthening and cold work hardening effects. When used as an alloying element, it can improve its strength and atmospheric corrosion resistance of the steel strip. However, when the content is too high, the cold stamping performance of the steel strip will drop sharply. At the same time, there will be segregation of the components of the continuous casting slab, causing uneven structure, increasing temper brittleness, and significantly reducing the plasticity and toughness of the steel strip, so that the steel strip will appear "cold brittle" phenomenon and brittle cracking during cold working. However, with the advancement of metallurgical technology, the segregation of P-containing steel leads to a significant reduction in the plasticity and toughness risks of the steel strip, creating conditions for the development of high-strength and high-weathering steel with high content. The P content of the present invention is 0.050% to 0.060%.
[0027] S: It is an impurity element in steel and is easy to form MnS in steel. The amount and shape of sulfides in steel directly affect the hole expansion performance of steel strip, especially strip sulfide inclusions are prone to cracks during deformation, so the designed S content is ≤0.003%.
[0028] Al: The basic function of the present invention is deoxidation in the steelmaking process. The content of Als in steel is generally less than 0.010%; at the same time, if the content of Als exceeds 0.060%, its grain refinement effect is weakened, so the present invention sets the Als content to 0.010% to 0.050%.
[0029] Cr: It can delay the pearlite transformation, significantly improve the hardenability of steel, facilitate the formation of bainite structure, and refine the structure to achieve a strengthening effect. Too high Cr content will deteriorate the processing and formability of the material. The principle of selecting the Cr content is to promote the formation of bainite and avoid the formation of martensite structure which has an adverse effect on elongation. Therefore, the Cr content in the present invention is 0.90% to 1.00%.
[0030] Ni: Ni can significantly improve the corrosion resistance of steel. At the same time, nickel and copper elements form a Ni-containing copper-rich phase and are retained in the outer oxide layer in a solid state, reducing the copper enrichment in the matrix and the chance of forming a liquid copper-rich phase, thereby avoiding hot brittleness defects. Therefore, Ni / Cu in steel is generally controlled to be ≥1 / 2, but too high nickel will increase the adhesion of the oxide scale, and pressing it into the steel will form hot rolling defects on the surface. Nickel is a precious metal, and too high a content will significantly increase the cost of steel alloys. Therefore, the Ni content in the present invention is 0.15-0.20%.
[0031] Cu: Cu is conducive to forming a dense, well-adhesive amorphous oxide (hydrocarbon oxide) protective layer on the surface of steel, and has a significant corrosion resistance. Copper and sulfur generate insoluble sulfides, thereby offsetting the harmful effects of S on the corrosion resistance of steel. According to the calculation formula of the atmospheric corrosion resistance index I, too little or too much copper content will reduce the calculated value of I. The peak value of Cu content is 0.35%, so the Cu content in the present invention is 0.30-0.35%.
[0032] V: Among all alloying elements, V is the most suitable element for producing stable and strong precipitation strengthening because the solubility product of V carbonitride is large, which leads to its solid solution temperature and greater solubility under higher temperature conditions. However, the solubility of V nitride is much lower than that of carbide, so VN formed by V and N plays a precipitation strengthening role in steel. Studies have shown that V (C, N) can induce the growth of grains and refine the structure after phase transformation by strain-induced precipitation at the austenite grain boundary, and the V (C, N) particles precipitated on the austenite grain boundary can provide more abundant nucleation sites for ferrite, and obtain finer ferrite grains when austenite transforms to ferrite; V (C, N) precipitates inside austenite, which can induce the nucleation of two ferrites, equiaxed ferrite and acicular ferrite, which can significantly improve the mechanical properties of steel; in addition, V has the effect of promoting the comparison of bainite. Therefore, the V content in the present invention is 0.0060% to 0.0070%.
[0033] N: Usually N element exists as an impurity element in steel, but N in V-containing steel can significantly increase the chemical driving force of V precipitation, increase the nucleation density of V (C, N), reduce the spacing between precipitated particles, and improve the precipitation strengthening effect; while the strengthening effect of V-containing steel by increasing N is irrelevant to the C content in the steel, and in addition, increasing N can also effectively reduce the size of precipitated particles. Therefore, the N content in the present invention is 0.060% to 0.070%.
[0034] Nb: Nb can pin austenite grain boundaries to prevent grain growth, ultimately refining the grains, which is beneficial to improving strength, plasticity, and toughness; but Nb is a precious metal, and excessive content thereof will significantly increase production costs; therefore, the Nb content in the present invention is 0.020-0.030%.
[0035] O: As a harmful element in steel, it is also an unavoidable element in the steelmaking process. The present invention achieves ultra-low oxygen content control through RH vacuum treatment, and the O content is ≤0.0020%.
[0036] In addition, the present invention also provides a method for preparing the above-mentioned VN microalloyed ultra-high strength weathering steel with a specification of ≤10 mm, comprising the following steps:
[0037] Step 1: sequentially carry out hot metal desulfurization, converter, RH vacuum treatment and LF refining to obtain molten steel that meets the chemical composition design requirements;
[0038] Step 2, feeding the molten steel obtained in step 1 into a continuous casting machine for slab continuous casting;
[0039] Step 3: heating the slab after continuous casting at a temperature of 1250±10°C for a heating time of 220 to 300 minutes, wherein the holding time is ≥35 minutes;
[0040] Step 4: Rough rolling the heated slab, the thickness of the intermediate slab at the rough rolling outlet is 40-55 mm, and then the intermediate slab is coiled and scaled using a hot coil box;
[0041] Step 5: Finish rolling the intermediate billet. When the finished product thickness is less than 6.0 mm, the finishing rolling inlet temperature is 1030-1080°C, and the final rolling temperature is 840-870°C; when the finished product thickness is 6.0-10.0 mm, the finishing rolling inlet temperature is 980-1020°C, and the final rolling temperature is 850-880°C;
[0042] Step 6: Cool the slab after finish rolling and then curl it at a temperature of 470-500°C. After coiling, place it in a slow cooling pit and slowly cool it to room temperature.
[0043] Among them, in the converter process of step one, high carbon ferromanganese is used for manganese and high manganese ferrochromium is used for chromium, and decarburization is not performed. Decarburization is performed during RH vacuum treatment, and then quantitative and precise carbon addition is performed in LF. The use of relatively cheap high carbon ferromanganese alloy can reduce the consumption of aluminum deoxidizer, and at the same time can greatly reduce iron loss and the oxygen content in the molten steel.
[0044] In step five, affected by the specification effect, in order to obtain 850MPa grade high-strength weathering steel with a thickness specification of ≤10mm, it is necessary to accurately control the rolling passes and the deformation amount of each pass, and finally a steel strip with a thickness of 3.0 to 10.0mm can be obtained.
[0045] Before coiling in step 6, the steel strip after finishing rolling is cooled in laminar flow by means of front-stage rapid cooling, with a laminar cooling rate of ≥60°C / s and a midpoint temperature of 520-550°C. During coiling, under the action of the strong hardenability element Cr, the coiling temperature is controlled at 470-500°C, which can ensure sufficient nano-level V(C,N) and NbC.
[0046] According to the above process, a weathering steel with a microstructure of bainite (B) + acicular ferrite structure (AF) + nano-precipitation phase (V(C, N), NbC) can be obtained. The mechanical properties of the steel are 850MPa-grade high-strength weathering steel with ReL≥720MPa, Rm≥850Mpa, and A≥17%. The 180° bending test at room temperature has no cracks at D=2a. In the low-temperature impact toughness test at -40°C, the V-notch impact energy of the 3 / 4 size specimen is KV2≥60J, and the V-notch impact energy of the 1 / 2 size specimen is KV2≥40J.
[0047] The present invention is further described below in conjunction with embodiments.
[0048] Example:
[0049] The present invention provides three groups of materials for comparative tests, the chemical compositions of which are shown in Table 1, and the remainder is Fe and unavoidable impurities.
[0050] Table 1
[0051]
[0052]
[0053] The process parameters of the billet heating, rough rolling, finishing rolling, laminar cooling, coiling, and the mechanical properties, bending properties, low temperature toughness, and microstructure types are shown in Table 2. Taking the parameters of Example 32 as an example, the metallographic structure obtained is as follows: Figure 1 shown.
[0054] Table 2
[0055]
[0056] According to the comparison of the above embodiments, it can be seen that by adopting the steel composition and production process provided by the present invention, the thickness of the steel strip finally obtained does not exceed 10 mm, and has higher yield strength and tensile strength, as well as better elongation.
Claims
1. A VN microalloyed ultra-high strength weathering steel with a specification of ≤10mm, characterized in that: The strength of the weathering steel is not less than 850Mpa, and includes the following components in mass percentage: 0.030≤C≤0.050%, 0.10%≤Si≤0.20%, 1.20%≤Mn≤1.30%, 0.050%≤P≤0.060%, S≤0.003%, 0.010%≤Als≤0.050%, 0.90%≤Cr≤1.00%, 0.15%≤Ni≤0.20%, 0.30%≤Cu≤0.35%, 0.060%≤V≤0.070%, 0.020%≤Nb≤0.030%, 0.0060%≤N≤0.0070%, O≤0.0020%, and the balance is Fe and unavoidable impurities.
2. A method for preparing VN microalloyed ultra-high strength weathering steel with a specification of ≤10mm, characterized in that: The method of using the VN microalloyed ultra-high strength weathering steel with a specification of ≤10 mm as claimed in claim 1, requiring the strength to be not less than 850 MPa, further comprising the following steps: Step 1: sequentially carry out hot metal desulfurization, converter, RH vacuum treatment and LF refining to obtain molten steel that meets the chemical composition design requirements; Step 2, feeding the molten steel obtained in step 1 into a continuous casting machine for slab continuous casting; Step 3: heating the slab after continuous casting at a temperature of 1250±10°C for a heating time of 220 to 300 minutes, wherein the holding time is ≥35 minutes; Step 4: Rough rolling the heated slab, the thickness of the intermediate slab at the rough rolling outlet is 40-55 mm, and then the intermediate slab is coiled and scaled using a hot coil box; Step 5: Finish rolling the intermediate billet. When the finished product thickness is less than 6.0 mm, the finishing rolling inlet temperature is 1030-1080°C, and the final rolling temperature is 840-870°C; when the finished product thickness is 6.0-10.0 mm, the finishing rolling inlet temperature is 980-1020°C, and the final rolling temperature is 850-880°C; Step 6: Cool the slab after finish rolling and then curl it at a temperature of 470-500°C. After coiling, place it in a slow cooling pit and slowly cool it to room temperature.
3. The method for preparing a VN microalloyed ultra-high strength weathering steel with a specification of ≤10 mm as claimed in claim 2, characterized in that: In the converter process of step one, high carbon ferromanganese is used for manganese and high manganese ferrochromium is used for chromium without decarburization. Decarburization is carried out during RH vacuum treatment, and then quantitative and precise carbon addition is carried out in LF.
4. The method for preparing a VN microalloyed ultra-high strength weathering steel with a specification of ≤10 mm as claimed in claim 2, characterized in that: Before coiling in step six, the steel strip after finish rolling is cooled in laminar flow by adopting the front-stage rapid cooling method, the laminar cooling rate is ≥60°C / s, and the midpoint temperature is 520-550°C.
Citation Information
Patent Citations
Method for improving utilization ratio of V-N micro-alloying high-strength steel vanadium alloy
CN101161843A
Method for improving performance of 700MPa grade V-N micro-alloying high-strength weathering steel
CN101161849A
Production method of vanadium nitrogen micro-alloying high-strength weathering resistant steel
CN102766826B